KOMUNIKASI ORGANISASI DINAS KEBUDAYAAN DAN PARIWISATA KABUPATEN TORAJA UTARA DALAM UPAYA PENGEMBANGAN PARIWISATA - BIDA, SITA SILAMBI; RURU, JOORIE MARHAEN; MAMBO, RULLY (JURNAL ADMINISTRASI PUBLIK, 2022)
Communication is one of the important factors in an organization that allows each member to exchange information and cooperate to achieve organizational goals. The purpose of this research is to describe and identify the communication of the Culture and Tourism Office of North Toraja Regency in the effort of Tourism Development. The research method used is descriptive qualitative with data collection techniques of observation, interviews and documentation. The data obtained were than analyzed using Miles and Huberman analysis techniques which consisted of data reduction, data presentation and conclusion drawing. The focus in this study refers to the dimensions of internal communication, which consist of vertical communication and horizontal communication. Based on the research results, the Deparment of Culture and Tourism of North Toraja Regency conducts organizational communication is accordance with the organizational structure where there are two flows of information delivery, namely vertically (top down and buttom up) and horizontally. Vertical communication is carried out to provide and convey information, reports, ideas or complaints related to work, while horizontal communication is carried out to coordinate various activities, programs and policies related to the implementation of the duties and functions of each field. Â Keywords: communication, organizational communication, tourism development